Fullerene and nanotube models in Bolyai - Lobachevsky hyperbolic geometry H3 on the 200th anniversary of its discovery - Emil Molnár; Jenő Szirmai (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2023)
The Archimedean solid (5, 6, 6), where regular pentagon, hexagon and hexagon surround each vertex, so altogether 60 vertices (with carbon atoms for C60  fullerene). 12 pentagons and 20 hexagons bound this football polyhedron, as a regular (say white) icosahedron truncated by 12 (black) pentagons at its 12 vertices.